Brain volumetric correlates of inhibition and cognitive flexibility 16 years following childhood traumatic brain injury. Issue 4 (4th July 2017) - Yu, Kelleynne; Seal, Marc L.; Reyes, Jonathan; Godfrey, Celia; Anderson, Vicki; Adamson, Chris; Ryan, Nicholas P.; Hearps, Stephen J. C.; Catroppa, Cathy
Abstract: Executive functions (EFs), such as inhibition and cognitive flexibility, are essential for everyday functioning, including regulation of socially appropriate emotional responses. These skills develop during childhood and continue maturing into early adulthood. The current study aimed to investigate the very long‐term impact of childhood traumatic brain injury (TBI) on inhibition and cognitive flexibility, and to examine whether global white matter is associated with these abilities. Twenty‐eight young adult survivors of childhood TBI (mean age at 16‐year follow‐up = 21.67 years, SD  = 2.70) and 16 typically developing controls (TDCs), group‐matched for age, sex, and socioeconomic status, completed tests of inhibition and cognitive flexibility and underwent structural MRI. Survivors of childhood TBI did not significantly differ from TDCs on EF or white matter volume. However, the relationship between EF and white matter volume differed between survivors of TBI and TDCs. Survivors of TBI did not mimic the brain behavior relationship that characterized EF in TDCs. The inverse brain behavior relationship, exhibited by childhood TBI survivors, suggests disruptions in the whole brain underpinning EF following childhood TBI. Abstract : Sixteen years following childhood traumatic brain injury (TBI), survivors did not differ from age‐matched controls on executive function measures and white matter volume. However, childhood TBI survivors did not reflect the typical brain behavior relationship that characterized executive function in adulthood, suggesting disruptions in the whole brain underpinning executive function.